Legal aspects of the termination of permanent management vis a vis the statutory management of State Forests - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2021)
The aim of the considerations presented in the article was to determine whether and if so, in what way, the management created with regard to real estate managed by the State Forests during the validity of the Act on land management and real estate expropriation may cease to exist. In the author's opinion, the State Forests’ management performed under the provisions of the Forest Act is not subject to termination in the manner that applies to the permanent management of real estate. The question that needs to be addressed and assessed is whether the termination of the management under the Act on land management and real estate expropriation requires a precise determination and, in particular, whether the said legislative act could apply to forest land covered by the decision confirming the right of management. It must also be considered whether the provisions of Article 2.1 or Article 4 of the Act of 29 September 1990 amending the Act on land management and expropriation of real estate should apply in such cases. Had the latter regulations applied, then the management created when the Act on land management and real property expropriation was in force, could not have been transformed into permanent management pursuant to Article 199 clause 2 of the Act on the management of real property.